COMMUNITY-BASED DA‘WAH IN ISOLATED AREAS: THE ROLE OF LOCAL FIGURES IN SUSTAINING RELIGIOUS LIFE IN TANJUNG GELUMPANG VILLAGE, ACEH TAMIANG - Naad, Darul; Abdullah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2026)
This This study aims to analyze the challenges of da‘wah and the dynamics of socio-religious change in remote rural areas, using a case study of Tanjung Gelumpang Village, Sekerak District, Aceh Tamiang Regency. This village is classified as an isolated area characterized by limited infrastructure access, the minimal presence of professional da‘is, and increasingly difficult geographical conditions due to recurrent flooding that has cut off land access and made river routes the only means of transportation. These conditions objectively constitute structural barriers to formal da‘wah activities. Nevertheless, this study reveals an interesting phenomenon in the form of a high level of religious practice and the sustainability of the village’s socio-religious life. This research employs a descriptive qualitative approach, with data collected through field observations, in-depth interviews with local religious leaders and customary figures, and documentation of community religious activities. The findings indicate that local actors-such as mosque imams, customary elders, and santri who have completed their pesantren education play a key role in sustaining community-based da‘wah. Da‘wah in this village does not rely on formal institutions but instead develops through social relations, exemplary conduct, and local wisdom that is internalized in the community’s everyday life. These findings emphasize that da‘wah in remote rural areas has distinct characteristics compared to urban da‘wah and requires a contextual approach that is adaptive to the social, cultural, and geographical conditions of the community. This study is expected to contribute both theoretically and practically to the development of community-based da‘wah concepts in marginal and isolated regions.